Deciphering the Allosteric Effect of Antagonist Vismodegib on Smoothened Receptor Deactivation Using Metadynamics Simulation - An, Xiaoli; Bai, Qifeng; Bai, Fang; Shi, Danfeng; Liu, Huanxiang; Yao, Xiaojun (Frontiers in Chemistry, 2019)
The smoothened receptor (Smo) plays a key role in Hedgehog (Hh) signalling pathway and it has been regarded as an efficacious therapeutic target for basal cell carcinoma (BCC) and medulloblastoma (MB). Nevertheless, the resistance mutation and active mutants of Smo have put forward the requirement of finding more effective inhibitors. Herein, we performed metadynamics simulations on Smo bound with vismodegib (Smo-Vismod) and with cholesterol (Smo-CLR) respectively to explore the inhibition mechanism of vismodegib. The simulation results indicated that vismodegib-induced shifts of TM5, TM6 and TM7，which permitted the extracellular extension of TM6 and extracellular loop3 (ECL3) to enter the extracellular cysteine-rich domain (CRD) groove. Therefore, an open CRD groove that has not been noticed previously was observed in Smo-Vismod complex. As a consequence, the occupied CRD groove prevents the binding of cholesterol. In addition, the HD and ECLs play crucial roles in the interaction of CRD and TMD. These results reveal that TM5, TM6 and TM7 play important roles in allosteric inhibition the activation of Smo and disrupting cholesterol binding by vismodegib binding. Our results are expected to contribute to understanding the allosteric inhibition mechanism of Smo by vismodegib. Moreover, the detailed conformational changes contribute to the development of novel Smo inhibitors against resistance mutation and active mutants of Smo.